Risk Assessment and Prevention of Spontaneous Preterm Birth - Chao Li; Yang Pan; Dan-Dan Shi (Maternal-Fetal Medicine, 2020)
Abstract. Preterm parturition is the consequence of pathological signals that activate the common pathway of parturition and considered as a syndrome. Many risk factors for spontaneous preterm birth (sPTB) have been identified. Two significant risk factors for sPTB are history of prior sPTB and short cervical length at midtrimester. 17 hydroxyprogesterone caproate, vaginal progesterone, cerclage, and pessary have all been studied for prevention of sPTB. Difference in patient populations likely contributes to the conflicting study results. Further studies are needed to establish strategies in prevention of sPTB in singleton as well as multiple pregnancies.